Transforming Consent Conversations: A Case Study on the Learning of Feminist Public Educators - Trefzger Clarke, Lisa (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2022)
This case study explores the experiences of nine female-identifying feminist public educators working with Ontario, Canada, sexual assault centres who regularly facilitate discussions about sexual consent and gender-based sexual violence in schools, post-secondary institutions, and community workshops. The educators discuss their experiences of adaptation and “inoculations” for inspiring transformative learning in their audiences, and the ways in which their practice and person have been transformed through their profession. With a focus on the relationships between intersectional feminist pedagogy, social justice education, transformative learning, and public pedagogy, the educators describe their resilience from trauma, critical thinking, and self-reflective practice, highlighting the benefits of co-facilitation, debriefing with colleagues, and mentorship.